Factors Influencing Maize Production in Rural Kenya: Case of Kisii County - Ombuki, Charles (My University, 2018)
Agricultural Sector in Kenya is the backbone of the country’s economy and the source of livelihood for majority of the rural population. The sector contributes about 26 percent of the country’s GDP, employs about 75 percent of the population and is a major source of food to Kenya’s growing population. Maize is an important cereal crop, holding a key position in Kenyan agriculture. Incidentally, Kenya has consistently produced less maize over the years than required to feed the population. With per capita maize consumption at 125kg, the country experienced a maize deficit of between 1.5 million and over 2.0 million metric tonnes during the period 2010 to 2015. For arid and semi arid lands, the challenge towards enhanced maize production has been harsh weather conditions. Proposed efforts to mitigate against such harsh weather conditions include, use of irrigation, transplanted maize (Zea mays) and adoption of drought resistant maize varieties. Kisii County however, is no exception to declining maize production over the years. This is despite the county enjoying favourable climatic conditions that favour agriculture. This study was carried to determine the factors influencing maize production in Kisii county. The study was motivated by an understanding that factors influencing maize production in arid and semi arid lands are already known while the same remain unclear in areas with suitable climatic conditions such as Kisii county which still experience declining trends in maize production. The target population was all farmers in Kisii county. A sample of 300 farmers from ten (10) wards was selected. The study used a multiple linear regression model to measure the relative effects of the various factors influencing maize production. Findings show that the key factors influencing maize production are land tenure system that is practiced, lack of use of high yielding maize varieties, household income, Number of extension visits and Acreage devoted to maize cultivation. Consequently, the study recommends change of land tenure system among members of the community to avoid wasting cultivable land through subdivisions. Further, the study recommends that farmers be encouraged to practice intensive farming and the county government to increase extension services so as to educate farmers on better farming practices.
Keywords: Maize Productivity; Land tenure